Extracorporeal shockwave therapy (ESWT) in the treatment of atrophic non-unions of femoral shaft fractures. (December 2015) - Kuo, Shu-Jui; Su, I-Chang; Wang, Ching-Jen; Ko, Jih-Yang
Abstract: Introduction: As of now, the role of extracorporeal shockwave therapy (ESWT) in the treatment of atrophic non-unions is inconclusive. The purpose of the study was to investigate the effectiveness of ESWT and the role of this technology in the treatment of atrophic non-union of femurs. Methods: We retrospectively analyzed 22 patients treated between July 1999 and September 2007 in our hospital with ESWT for atrophic non-unions of isthmic femoral shaft fractures that were initially treated surgically using closed reamed nailing procedure. Patients with open fractures, skeletal immaturity, on anti-osteoporotic medications, with infections, pathological fractures, smokers, with systemic disease compromising bone healing, and excessive deformity were excluded from this study. Due to incomplete follow-up one (1) patient who moved abroad after ESTW treatment was not included in this study and as part of the 22-patients cohort. Radiographs were obtained before treatment and once a month after treatment for 12 months. Results: Using ESWT we showed that 14 fractures out of 22 (63.6%) achieved bony union with an average union time of 9.2 months (range 6–13 months). The union rate was 100% (8 of 8 cases) when ESWT was performed within 12 months from closed reamed nailing surgery versus 42.9% (6 of 14 cases) when ESWT was performed after 12 months from initial surgery. The eight (8) patients out of the total 22 patients cohort, who did not achieve bony union after ESWT, received subsequent treatment with bone grafting with augmentative plating surgery and all achieved bony union within 5 months after intervention. Conclusion: For patients with atrophic non-unions of femoral shaft fractures, ESWT can be used as an alternative and effective non-invasive method of treatment. ESWT treatment does not negatively influence/compromise previous surgeries and if needed it can be followed by additional surgeries without any complications. Highlights: ESWT can be utilized for atrophic non-unions of femoral shaft fractures. The success rate of ESWT can be as high as 100%, if applied within 12 months after the initial treatment. ESWT will not jeopardize subsequent bone grafting surgeries, if ESWT fails.